Inovasi Si ADiT GerAH Sebagai Upaya Pengendalian Penyakit Tidak Menular - Anggorodiputro, Raden Roro Ratuningrum; Hanipah, Sansan Nurul; Paryono, Jendi Ari (FKM UIN Sumatera Utara Medan, 2023)
Hypertension and diabetes mellitus are major challenges in Indonesia. These two diseases are most often found in health services with a fairly high prevalence. It is important to do early detection of diabetes mellitus and hypertension in order to optimize management if detected and the public also needs to be educated so they understand the importance of having their health status checked. The importance of innovation in overcoming non-communicable disease problems in society with the aim of making people aware of the importance of hypertension and diabetes screening and monitoring of sufferers. The SI AdiT GerAH innovation is an innovation to control Non-Communicable Diseases with modifications such as cooking demonstrations and the involvement of cadres and families in monitoring people with diabetes and hypertension as well as the existence of stickers intended as a sign that the community must be aware of emergencies for sufferers.